Boron neutron capture therapy for oral precancer: proof of principle in an experimental animal model - Monti Hughes, Andrea (2013)
OBJECTIVES: Field-cancerized tissue can give rise to second primary tumours, causing therapeutic failure. Boron neutron capture therapy (BNCT) is based on biological targeting and would serve to treat undetectable foci of malignant transformation. The aim of this study was to optimize BNCT for the integral treatment for oral cancer, with particular emphasis on the inhibitory effect on tumour development originating in precancerous conditions, and radiotoxicity of different BNCT protocols in a hamster cheek pouch oral precancer model. MATERIALS AND METHODS: Groups of cancerized hamsters were locally exposed to single or double (2 or 4 weeks apart) applications of BNCT at different dose levels, mediated by the boron compounds boronophenylalanine (BPA) or BPA and decahydrodecaborate (GB-10) administered jointly. Cancerized, sham-irradiated hamsters served as controls. Clinical status, tumour development from field-cancerized tissue and mucositis were followed for 8 months. RESULTS: A double application (4 weeks apart) of BNCT mediated by GB-10+ BPA at a total dose of 10 Gy in two 5-Gy doses rendered the best therapeutic advantage (63-100% inhibition of tumour development from field-cancerized tissue), minimizing dose-limiting mucositis. CONCLUSION: BNCT can be optimized for the integral treatment for head and neck cancer, considering the implications for field-cancerized tissue.